INFLUENCE OF PURIFICATION PROCESS ON THE CHARACTERISTICS OF ROMANIAN CALCIUM BENTONITE (Journal of Engineering Studies and Research, 2016)
A calcium bentonite from Orasu Nou deposit (Romania) was used as raw material. The natural bentonite provided by S.C. Bentonita S.A., Satu Mare has the following mineralogical composition: 57 % montmorillonite, 40 % cristobalite, and 3 % quartz. Due to the relatively high percentage of impurities in natural calcium bentonite, we decided to purify the raw material, in order to improve the quality of montmorillonite. Through purification procedure, well defined granulometric fractions with particles of less than 2 μm, are obtained. The crude and purified calcium bentonites were characterized by textural analysis, scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX). The physical, structural and morphological characteristics are affected by the purification process. The purified bentonite can be used to obtain advanced materials, which can be tested as adsorbents for environmental remediation.
Keywords: montmorillonite; purification; surface area; pore volume; pore diameter; adsorption-desorption isotherm; microscopy